Distribution and conservation status assessment of the freshwater fishes in the Krom River system in the Eastern Cape Province, South Africa - Mthombeni, Annah (Rhodes University, Faculty of Science, Department of Ichthyology and Fisheries Science)
The Cape Fold Ecoregion (CFE) contains the highest number of endemic freshwater fishes in Africa, south of the Zambezi River system. The CFE's unique fish fauna has, however, suffered severe decline in historical distribution ranges and population sizes due to multiple impacts, with the two main threats being introduced invasive piscivores and habitat degradation. Growing evidence shows that biodiversity is being lost at unprecedented levels due to increased human pressure and demand for limited resources. Future projections also indicate high extinction risk, particularly for freshwater ecosystems, as a result of global climate change. Yet for many regions, including the CFE, there is still limited biodiversity knowledge to guide decision making processes. The Krom River system in the eastern Cape Fold Ecoregion (CFE) contains three native freshwater fish species. These are Pseudobarbus senticeps, which was recently revalidated, Sandelia capensis and a galaxiid lineage currently informally referred to as Galaxias zebratus sp. 'Joubertina'. Two of these taxa are listed under threatened categories of the International Union for Conservation of Nature (IUCN). These are P. senticeps, which is listed as Critically Endangered and Galaxias zebratus sp. 'Joubertina', which is listed as Endangered. Although S. capensis is currently listed as Data Deficient, the most recent information indicates that the species comprises three allopatric lineages, with the Krom River population belonging to a lineage that is distributed across a number of river systems on the south coast. Two non-native fishes, Micropterus salmoides and Lepomis macrochirus, have also been introduced into this river system. Updated information on distribution patterns and habitat utilisation is required to guide authorities to develop effective management plans and conservation of the threatened fishes of the Krom River system. The aim of this study was to determine the current distribution of the fishes of the Krom River system and to provide recommendations for in situ conservation measures to protect remnant populations and promote recovery and range expansion of the native fishes. The primary objective of the study was to use historical and present data to map the distributions patterns. Data on the distribution of the fishes of the Krom River system were obtained from various sources, including the NRF-SAIAB database, studies published in peer reviewed literature and unpublished reports. Systematic sampling was conducted in the Krom River system and several of its tributaries to provide a snapshot of the current distribution of both native and non-native fishes in this system at the time of this study. The presence of instream physical barriers was recorded, and habitat and water quality were visually assessed. Only four species of freshwater fishes were recorded during the surveys. These were two native species, the Krom River redfin P. senticeps and the Cape kurper Sandelia capensis, and two introduced species, the black bass M. salmoides and bluegill sunfish L. macrochirus. Pseudobarbus senticeps was the most common and widely distributed species in the system, and was recorded at 20 localities (four mainstem and 16 tributary localities). Sandelia capensis was less common and was recorded at only eight localities (four mainstem and four tributary localities). These two native species co-occurred at all the eight localities where S. capensis was recorded, but P. senticeps was always more abundant than Sandelia. Micropterus salmoides was recorded at six localities (four mainstem and 2 tributary localities) while L. macrochirus was recorded at five localities (four mainstem and one off-stream dam site). Native fishes were not recorded at sites where non-native fishes were present except at two localities in the Wit Els River where juvenile M. salmoides were found amongst the native fish samples. However, unlike the other localities where all size classes (i.e., young of the year, juveniles, subadults and adults) were present, only adult redfins were found in the Wit Els River where juveniles of largemouth bass occurred. A comparison of the past and present distribution patterns of the native fishes indicates a considerable decline in distribution range, and remnant populations are now fragmented compared to past observations. The major threats and impacts on the Krom River system are the presence of non-native piscivores, construction of instream physical barriers, and agricultural activities. The information from this study could form a basis for establishing long-term conservation measures that should focus on preventing the spread of non-native fishes, and rehabilitating critical habitats for the future persistence of remnant populations of native fishes. The study also evaluated the implications of incomplete taxonomy on conservation status assessments and prioritisation, by evaluating case studies of species complexes of freshwater fishes whose taxonomy has been recently resolved, as well as two complexes with lineages that await formal recognition as distinct species. The aim was to demonstrate how incomplete knowledge of taxonomy affects the assessment of extinction risk and can potentially misdirect conservation prioritisation. Specifically, the study examined how change in taxonomy or recognition of undescribed genetic lineages in faunal listings affects range size and IUCN Red List risk category. The study taxa were Pseudobarbus afer sensu lato (sl), Enteromius anoplus sl, Amphilius natalensis sl, Sandelia capensis and S. bainsii, and the study assessed the species complexes as Least Concern or Near Threatened. The majority of these taxonomically revised species and genetic lineages were determined to be Critically Endangered (CR), Endangered (EN) and Vulnerable (VU), as the extent of occurrence was estimated to be < 100 km2; < 5000 km2 and < 20 000 km2 respectively. The species and lineages have been observed in fewer than ten locations, and the populations have been observed to be in decline. The results of this study indicate that the current taxonomic status of the native species in the Krom River system obscures the diversity of these fishes and affects conclusions for conservation assessments. Findings from this preliminary assessment highlight the need for advancing taxonomic knowledge through accurate delimitation of species boundaries, particularly within
Keywords: Cape Fold Belt (South Africa); Freshwater fishes -- South Africa Kromme River (Eastern Cape); Freshwater fishes Conservation; Freshwater fishes Geographical distribution; Aquatic biodiversity -- South Africa Kromme River (Eastern Cape); Habitat (Ecology); Freshwater fishes Climatic factors